2013
DOI: 10.3389/fimmu.2013.00033
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Activate Tumoral CORTACTIN to Enhance Progression of Orohypopharynx Carcinoma

Abstract: CORTACTIN is an actin-binding protein critically involved in cellular migration and invasion. Here, we investigated the role of CORTACTIN in the pathophysiology of orohypopharynx carcinoma – one of the major subtypes of head and neck cancer. To this end, we analyzed CORTACTIN expression in tumor tissues from 89 orohypopharynx carcinoma patients in relation to clinical parameters. We found that high tumoral CORTACTIN expression associated with poor survival, higher T-stage, and higher lymph node metastasis (N-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
(56 reference statements)
5
29
0
1
Order By: Relevance
“…Cortactin is required for invadopodia formation (33), and it converges different pathways leading to cancer invasion. The increase in cortactin phosphorylation reported here is similar to earlier observations by Dumitru and colleagues (16) in oropharyngeal cancers. The changes in matrix degradation induced by neutrophils are not as robust as the overall changes in invasion observed in the Transwell assays or invadopodia formation.…”
Section: Cells Invadopodia Have Been Identified In Numerous Invasivesupporting
confidence: 82%
See 2 more Smart Citations
“…Cortactin is required for invadopodia formation (33), and it converges different pathways leading to cancer invasion. The increase in cortactin phosphorylation reported here is similar to earlier observations by Dumitru and colleagues (16) in oropharyngeal cancers. The changes in matrix degradation induced by neutrophils are not as robust as the overall changes in invasion observed in the Transwell assays or invadopodia formation.…”
Section: Cells Invadopodia Have Been Identified In Numerous Invasivesupporting
confidence: 82%
“…They also observed an increase in expression of MMP9 and CCL4 by CD66b-positive cells in human tumor sections (15). In a follow-up publication, Dumitru and colleagues (16) have shown that neutrophils increased cortactin phosphorylation in squamous cell carcinomas, promoting cancer migration. This finding is particularly important because metastatic spread is associated with the formation of specialized subcellular structures regulated by cortactin phosphorylation called invadopodia (17,18).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was not possible to assess the independent prognostic utility of cortactin in a multivariate model for OS or DFS given the small number of events in the present cohort. Nonetheless, our findings validate the reported association of cortactin with OPC patient outcome in a univariate analysis model (37).…”
Section: Prognostic Significance Of Cortactin In Opc-supporting
confidence: 81%
“…In accordance with our findings, high tumor CTTN expression has been shown to correlate with increased aggressiveness and poor outcome in many cancers, but most frequently in HNSCC (37,45). A recent pre-clinical study reported tumor radiosensitization via abrogation of the ␤1-integrin/FAK/cortactin/JNK1 signaling axis by administration of an anti-␤1-integrin antibody in vitro and in vivo, making this pathway a therapeutically attractive target for investigation in OPC (35).…”
Section: Fig 5 Model For Radioresistance Mediated By Cortactin In Hsupporting
confidence: 74%